基于Marc对塑料-金属斜齿轮副黏弹性的有限元分析 - 郝一舒; 祝标; 赵星龙 (Jixie chuandong)
Plastics performance is affected greatly by temperature,as for plastic gear pair,the temperature field is influenced by the load or torque.The viscoelasticity characteristic of plastic helical gear is simulated by using Prony series in nonlinear finite element software Marc.The finite element simulation analysis of the meshing of plastic helical gear and steel gear is carried out in Marc by using multiphysics coupling theory.The influence of viscoelasticity on meshing temperature field during meshing process is obtained by comparing the finite element analysis result under different load and torque conditions.